Implementasi Pendidikan Islam melalui Kegiatan Majikan (Masyarakat Ngaji Kitab Sesarengan) di Desa Jatiluhur Kecamatan Rowokele Kabupaten Kebumen - Tri Muryanti; Robingun Suyud El Syam; Rifqi Aulia Rahman (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of the Majikan (Sesarengan Book Study Community) activities, identify supporting and inhibiting factors in the implementation of activities, and examine the contribution of the “Majikan” activities to the development of Islamic education in the community. This study uses a qualitative approach taking the object of the implementation of Islamic education through the “Majikan” activities located in Jatiluhur Village, Rowokele District, Kebumen Regency, with research subjects including the chairman of GP Ansor, the administrators of the “Majikan” activities, religious leaders, and the congregation participating in the “Majikan” activities. Data were obtained through in-depth interviews, observations, and documentation to then be analyzed descriptively. The results of the study indicate that the Majikan (Sesarengan Book Study Community) activities in Jatiluhur Village are carried out consistently as a form of community-based non-formal Islamic education. These activities include reading sholawat, studying fiqh books regarding basic worship using the bandongan method, as well as closing prayers and mushafahah. This activity was driven by community involvement and support from the village government, despite challenges such as differences in educational backgrounds, time constraints, weather conditions, and location. The contribution of the "Majikan" program is to improve religious understanding, foster appropriate worship behavior, strengthen Islamic brotherhood, and raise social awareness through alms management.